Case report of hidradenitis suppurativa localized to the face in an HIV patient - Brian D Rankin (SAGE Publishing, 2021)
Hidradenitis suppurativa is a chronic, debilitating inflammatory skin disease. Case reports of individuals with hidradenitis suppurativa presenting exclusively on the face, as well as reports of individuals with HIV and hidradenitis suppurativa, are rare. Here, we present the case of an HIV-positive man who presented with hidradenitis suppurativa localized only on his face. We also review facial hidradenitis suppurativa and hidradenitis suppurativa in HIV patients.